Beyond standardized english: Review of englishes from 20th century independent countries (Audiobook). (2023)
With the purpose of teaching English from a historical approach, and making its development and influence visible from a decolonial perspective, this project of creation and interpretation under the line of research: Representative and imaginary discourses in social educational action; through a historical investigation of twentieth century independent countries which commonality is the appreciation of English in their cultural practices; and artistic expression (artistic makeup), aims to create an audiobook that allows visualization of other faces beyond the standardized English. Thus, Englishes are needed for a broader view in ELT as well as to enrich the cultural perception in and of the language.